Seed and seedlings quality of Anadenanthera colubrina (Vell.) Brenan harvested in Paraná State, Brazil - Cruz, Maria Soraia Fortado Vera; Malavasi, Marlene de Matos; Ristau, Ana Carolina Pinguelli; Malavasi, Ubirajara Contro; Dranski, João Alexandre Lopes; Braz, Hannah (Scientia Agraria Paranaensis, 2022)
The place of harvest influences the quality of the seeds and, consequently, the quality of the seedlings formed. Thus, the work aimed to quantify the influence of harvesting place on the physiological potential of seeds and on the quality of A. colubrina seedlings. The lots refer to the seed harvesting locations, Marechal Cândido Rondon (MCR), Diamante D’Oeste (DO) and Santa Helena (SH). The design was completely randomized. For seed quality, the thousand weight, percentage, average germination time (AGT) and germination speed index (GSI), dry seedling mass (DSM) and respiration rate (RESP) were evaluated. For seedling quality, height, stem diameter, shoot, root and total dry biomass, Dickson quality index, and root electrolyte loss were evaluated. For the DO+SH, the unfolding of the correlations indicated the AGT as the most influential characteristic, both with a direct and indirect effect on the basic variables, that is, seedling quality. Additionally, it is noteworthy that the characteristics evaluated stem diameter, total dry mass of the plant and root electrolyte loss, proved to be good indicators of the quality of seedlings of A. colubrina, presenting themselves quite responsive in the correlation analysis. The place of harvest influenced the quality of seeds and seedlings of Anadenanthera colubrina, with the distinction of origins into two groups: seed lot from MCR and DO+SH. Germination attributes contributed to explain the effects of seed lot quality on seedling quality and can be used to select better quality seeds and seedlings.